Effect of salt stress and nitrogen supply on seed germination and early seedling growth of three coastal halophytes - Yanfeng Chen; Yan Liu; Lan Zhang; Lingwei Zhang; Nan Wu; Huiliang Liu (PeerJ, 2022)
Due to high salinity and low nutrient concentrations, the coastal zone is considered as one of the most vulnerable of the earth’s habitats. Thus, the effect of salt and nitrogen on growth and development of coastal halophytes has been extensively investigated in recent years, but insufficient attention has been paid to the crucial stages of plant establishment, such as seed germination and seedling growth. Thus, we carried out a field experiment to evaluate the effects of salt stress (6, 10 and 20 g/kg NaCl) and nitrogen supply (0, 6 and 12 gm−2year−1) on seed germination and seedling growth of three coastal halophytes (including two dominant herb species Glehnia littoralis and Calystegia soldanella, one constructive shrub species Vitex rotundifolia) from September 2020 to June 2021. The results of our experiment showed that seeds of G. littoralis exhibited an explosive germination strategy in the early spring of 2021 with 70% of the seeds germinating. Conversely, the seeds of V. rotundifolia exhibited slow germination in the late spring of 2021 with only 60% of the seeds germinating. C. soldanella seed germination exhibited two obvious peak periods, but only 6% of the seeds germinated, which means that most seeds may be stored in the soil by stratification or died. All three halophytes showed greater sensitivity to nitrogen than salt stress during the seed germination stage. Nitrogen supply significantly delayed seed germination and reduced the cumulative germination percentage, particularly for G. littoralis. Despite the large impact of nitrogen on seed germination, nitrogen had a larger impact on seedling growth suggesting that the seedling growth stage of halophytes is more vulnerable to changes in nitrogen supply. Moreover, nitrogen supply significantly reduced the individual biomass of G. littoralis, C. soldanella and V. rotundifolia, with greater decreases seen in the dominant species than in the constructive species. Conversely, nitrogen supply increased underground biomass allocation of G. littoralis and C. soldanella, suggesting that the constructive species were less sensitive to nitrogen and exhibited a stronger anti-interference ability than the dominant species. Therefore, increasing nitrogen supply may firstly affect the seed germination and seedling growth of the dominant species, but not the constructive species.